Potential antioxidant and anti-inflammatory effects of Erythroxylum cuneatum (Miq.) Kurz leaf extract against oxidised low-density lipoprotein in human aortic endothelial cell - Shanmugam, Nitya (2020)
Oxidative stress and inflammation are known to be associated with the pathogenesis of most chronic diseases such as atherosclerosis, cancer and diabetes. Medications like nonsteroidal anti-inflammatory drugs are commonly used to treat the diseases but are accompanied by adverse effects. Erythroxylum cuneatum (EC), also known locally as “Chinta mula”, belongs to the Erythroxylaceae family. Scientific evidence for the medicinal properties of the plant is still limited. Therefore, this study aims to determine the antioxidant and anti-inflammatory properties of EC leaf extract for the prevention of atherosclerosis in vitro. The study was divided into two phases. The first phase is screening of EC leaf extract using four solvents, namely acetone, water, hexane and ethanol. The four different types of EC leaf extracts were analysed for preliminary phytochemical screening individually. The antioxidant activity was tested by total phenolic content (TPC), 2,2-diphenyl-1-picrylhydrazyl (DPPH) and hydrogen peroxide (H2O2)-scavenging activity. Based on Phase 1 results, acetone and ethanol extracts were chosen to test the antioxidant and anti-inflammatory properties in vitro with oxidised low-density lipoprotein (oxLDL)-induced human aortic endothelial cells (HAoEC). Cell viability assay of EC leaf extract was conducted to determine the number of viable cells by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay. Antioxidant activity was determined by thiobarbituric acid reactive substances (TBARS) assay, reactive oxygen species (ROS) assay and nitric oxide (NO) production assay. The anti-inflammatory effects of EC leaf extract in HAoEC were determined by U937 cell monocyte adhesion and migration assay. The expression of adhesion molecules, namely human soluble intracellular adhesion molecule-1 (ICAM-1) and human soluble vascular cell adhesion molecule-1 (VCAM-1) were quantified using ELISA kit. Phase 1 results showed the presence of alkaloids, flavonoids and tannins in the acetone and ethanol extract. Phenols were found only in acetone extract while saponins were detected only in water extract. Additionally, acetone extracts exhibited the highest TPC and DPPH scavenging activity, while ethanol extract showed the highest H2O2-scavenging activity. Both extracts in Phase 2 inhibited lipid peroxidation and ROS production. They were also able to increase NO production indicating their antioxidant activity. Acetone extract was able to inhibit lipid peroxidation, ROS production and increase NO production better than ethanol extract at 80 μg/ml. Both extracts showed anti-inflammatory activities by reducing monocyte adhesion and migration and expression of ICAM-1 and VCAM-1. Acetone extract was able to inhibit monocyte adhesion and expression of ICAM-1 better than ethanol extract. While, ethanol extract showed significantly better inhibition of monocyte migration and expression of VCAM-1 than acetone extract. This study showed that EC acetone and ethanol extracts have high antioxidant activity among the four extracts. Both extracts showed antioxidant and anti-inflammatory activity in HAoECinduced with oxLDL. Generally, acetone extract at 80 μg/ml showed better antioxidant and anti-inflammatory activities than ethanol extract.